Análise de viabilidade de implantação de um centro de integração logística na região amazônica: um estudo de caso no Estado do Pará - HAGE NETO, Demétrio Dib (Universidade Federal do Pará, 2023)
The celebrated and constant evolution of operating operations and market companies compensate for the integration of process participants and the need to promote new operating strategies, as well as the integration of process participants, as well as the need for integration of participants in the process. process. resources involved in the supply chain. from this scenario of need for evolution and modification of market relations, the use and implementation of outstanding projects of logistics integration centers as a way of improving the logistics reality. Corroborating this reality, the main objective of this research was to verify the feasibility and benefits generated from the implementation of a Logistics Integration Center in the State of Pará - CILOG, from the perspective of the demand for production flow, availability of modal and location. To verify the feasibility of production for implementation, foam consulted without data regarding load states and load locations in adjacent areas, as well as potential, functionalities and resources of the implementation systems, with flow as the main centers of selection and, systematic and systematic way, of the feasibility and evaluation of the benefits generated from the implementation of the needs of the demand for services of attendance of the neighboring states, as well as of the entrances for the attendance of the neighboring states demand of flow of the production, availability of modals and geographic location . For this, an A-SWOT hybrid methodology was applied to define the HP location criteria and the decision factors that characterize the implementation of logistics such as the Logistics Integration Center (CILOG) in the Amazon Region, as well as the definition of the best for this implementation. , based on three local alternatives: Santarém (on the banks of the Amazon River), Alça Viária (on the banks of the Guamá River) and Miritituba (on the banks of the Tapajós River).